(untitled) (Fiep Bulletin - online, 2014)
The kinesiology was born in the 60s in America through the work of George Goodhearth (1918 - 2008). He worked mainly on the structure and on the muscles and began his study using muscle testing to determine the effectiveness of its treatments, examining a number of muscles before and after a re-alignment of the spine. The purpose was to receive information if and how much had been effective manipulation carried out by him for the trouble taken in treatment. Attaverso this study, however, noticed that people shortly after the rebalancing ritorrnavano to have pain and muscle stiffening, just as from the initial situation, therefore, the work was repeated altogether and began to make other attempts, acts to find more stable solutions, then more lasting in time. He realized that by stimulating specific reflex in certain areas of the body obtained a reinforcement of muscles located in parts of the body away from the reflection stimulated and that this was much more effective than applications made on the muscle itself. In addition, he found that these points were part of a larger group of reflex points (known as Chapman’s reflexes and reflections neurolymphatic) that had been identified Frank Chapman, and that helped to improve the lymphatic system.